The Ethics of Human Enhancement and Ferrando’s Philosophical Posthumanism - LaGrandeur, Kevin (Journal of Posthumanism, 2021)
Francesca Ferrando’s book Philosophical Posthumanism concentrates on some of the ethical issues connected with genetic alteration of the human species. Â In sympathy with her analysis, this brief article (commentary) elaborates on a parallel topic: the ethical implications of current projects to modify humans and their society with digital emerging technology.